PEMBELAJARAN KOOPERATIF TIPE NHT DALAM MEMBELAJARKAN KEMAMPUAN BERPIKIR KRITIS SISWA: ANALISIS VALIDITAS PERANGKAT PEMBELAJARAN - Marzuki Ahmad Lubis; Toharuddin Harahap; Dwi Putria Nasution (JURNAL MathEdu (Mathematic Education Journal), 2021)
Learning devices are part of supporting the learning atmosphere in order to achieve the desired goals. Without the support of good learning tools, it is very difficult to create effective learning. To ensure the implementation of good learning, learning tools are needed that meet various aspects, one of which is the validity of learning tools. This study aims to describe the level of validity of the Numbered Head Together (NHT) cooperative learning device in teaching students' critical thinking skills in mathematics. This type of research is a quantitative descriptive research. The subject of the research is a learning device which includes lesson plans and student activity sheet (SAS) on the material of Relations and Functions for students of SMP/MTs class VIII. The object of research is the level of validity of the learning device. The instrument used is a learning device validation sheet which includes a lesson plan validation sheet and a SAS validation sheet. Data was collected through filling out the learning device validation sheet from five validators to get assessments and suggestions for learning tools. The results of the analysis of the validation sheet show that in general the RPP meets the valid criteria with a validity index of 0.74 and the SAS also meets the valid criteria with a validity index of 0.73. Thus, it is concluded that cooperative learning tools in teaching students' critical thinking skills in mathematics are valid.